2012
DOI: 10.4161/cc.11.6.19453
|View full text |Cite
|
Sign up to set email alerts
|

YAP oncogene overexpression supercharges colon cancer proliferation

Abstract: The transcriptional co-activator YAP is an evolutionarily conserved regulator of organ size and progenitor cell proliferation. YAP is overexpressed at high frequency in many common human cancers and can directly drive cancer development in mouse models. YAP abundance and nuclear localization are negatively regulated by the Hippo kinase cascade, which, in epithelia, is activated by physiological cell-cell contact. Recent work in intestinal epithelium has established that YAP is constitutively inhibited by the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 80 publications
5
105
1
2
Order By: Relevance
“…Studies have demonstrated that YAP was overexpressed in human colon cancer specimens and cell lines. Overexpression of YAP promoted the growth and survival of colon cancer cells, which was indicative of its oncogenic function and suggested that its overexpression is a substantial contributor in cancer development (8)(9)(10). In addition, studies have confirmed that TAZ is upregulated in CRC and has an important role in CRC progression via promoting cell proliferation and survival (11)(12)(13).…”
Section: Introductionmentioning
confidence: 90%
“…Studies have demonstrated that YAP was overexpressed in human colon cancer specimens and cell lines. Overexpression of YAP promoted the growth and survival of colon cancer cells, which was indicative of its oncogenic function and suggested that its overexpression is a substantial contributor in cancer development (8)(9)(10). In addition, studies have confirmed that TAZ is upregulated in CRC and has an important role in CRC progression via promoting cell proliferation and survival (11)(12)(13).…”
Section: Introductionmentioning
confidence: 90%
“…These observations are compatible with the idea that Yap acts as an oncogenic regulator for cancer development. Increased expression and activity of Yap is associated with the growth, metastatic potential, and poor prognosis of several cancer types, including liver cancer and colorectal cancer (19,24,50).…”
Section: Discussionmentioning
confidence: 99%
“…The latter was initially described in drosophila for its ability to control organ size (19). Its role in EMT was demonstrated by studies in which nonphosphorylated (active) Hippo transducers YAP, TAZ, and TEAD were found to act either together, in conjunction with b-catenin/TCF, or with Smads (20,21) to induce genes that regulate cell morphology, migration, and cancer metastasis. Phosphorylation (inactivation) of the Hippo transducers is carried out by upstream kinases (Mst/Lats) resulting in their cytoplasmic retention and either proteasomal degradation (22) by the GSK3-b-associated degradation complex or sequestration of b-catenin and Smads thereby inhibiting the trans-activation of these transcription factors (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%